Category of Equity in the Context of the Luxury Tax Implementation// European Journal of Law and Public Administration - Krainii, Pavlo (Lumen Publishing Houseon, 2019)
The luxury tax is one of the most discussed taxes to make possible the introduction of a policy of social equity, which is extremely relevant and in demand. It is worth noting that the category of "equity" is certainly a basic category, which plays a significant role in the formation of the concept within which such a tax policy is implemented. Despite its comprehensive significance, the concept of equity is an important social ideal that helps to realize the luxury tax. One way or another, throughout history and within various forms of state, government and political systems, there have been implemented luxury taxes. Although not every time, the concept of "equity" played a decisive role in such a process. However, in the XXI century, it is impossible to imagine the necessity ofintroducing a luxury tax was accompanied by any other concept than the ideal of "equity".
Keywords: Research Subject Categories::LAW/JURISPRUDENCE